The Hawthorne Effect in Infection Prevention and Epidemiology. (18th September 2015) - Chen, Luke F.; Vander Weg, Mark W.; Hofmann, David A.; Reisinger, Heather Schacht
Abstract : The Hawthorne Effect is a prevalent observer effect that causes behavioral changes among participants of epidemiological studies or infection control interventions. The purpose of the review is to describe the origins of the Hawthorne Effect, to understand the term in relation to current scientific literature, to describe characteristics of the Hawthorne effect, and to discuss methods to quantify and overcome limitations associated with the Hawthorne Effect. Infect. Control Hosp. Epidemiol. 2015;36(12):1444–1450